Analysis Of Providing Compensation In Improving Employee Performance According To An Islamic Economic Perspective (Case Study Of Pt. Sarana Lampung Ventura) - Naufal Arfani, Muhammad; Fuadi, Fatih; Pratomo, Dimas (Dinasti Publisher, 2024)
This think about looks at the crossing point of Islamic financial standards and stipend hones in making strides representative execution, centering on PT. Sarana Lampung Ventura, an Indonesian wander capital company. Through subjective library inquire about, the consider analyzes how Islamic-based recompense frameworks adjust with modern human asset administration hones and their affect on representative efficiency, work fulfillment, and organizational commitment. The discoveries uncover that PT. Sarana Lampung Ventura’s recompense hones, counting reasonable compensation, convenient installments, and profit-sharing plans, for the most part adjust with Islamic financial standards. This arrangement contributes to expanded representative efficiency, upgraded work fulfillment, and lower turnover rates. In any case, challenges continue in adjusting advertise weights with strict adherence to Islamic standards and creating comprehensive measurements for representative commitments. The consider proposes a few suggestions to assist upgrade the company’s remuneration framework, counting executing a comprehensive execution administration framework that joins both monetary and non-financial measurements adjusted with Islamic values, growing representative benefits to reflect Islamic social obligation, and presenting skill-based pay components. This inquire about contributes to the developing body of writing on Islamic human asset administration, advertising experiences into the down to earth application of Islamic financial standards in present day trade settings. It highlights the potential for Islamic-based recompense hones to drive worker execution whereas keeping up moral and devout keenness. The consider concludes that whereas PT. Sarana Lampung Ventura has made noteworthy advance in adjusting its emolument hones with Islamic standards, there’s room for advance upgrade to reinforce its framework and possibly lead to indeed more noteworthy worker execution and organizational victory inside the system of Islamic financial matters.